Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the given system of equations:
1. [tex]\( y = x + 4 \)[/tex]
2. [tex]\( y = x^2 + 2 \)[/tex]
We need to find the points of intersection, which means we set the two equations equal to each other.
[tex]\[ x + 4 = x^2 + 2 \][/tex]
Re-arrange the equation to standard quadratic form:
[tex]\[ x^2 - x - 2 = 0 \][/tex]
We solve this quadratic equation using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -2 \)[/tex].
Calculate the discriminant ([tex]\( \Delta \)[/tex]):
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = (-1)^2 - 4(1)(-2) \][/tex]
[tex]\[ \Delta = 1 + 8 \][/tex]
[tex]\[ \Delta = 9 \][/tex]
Now, find the roots using the quadratic formula:
[tex]\[ x = \frac{-(-1) \pm \sqrt{9}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{1 \pm 3}{2} \][/tex]
This gives us two solutions for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{1 + 3}{2} = 2 \][/tex]
[tex]\[ x = \frac{1 - 3}{2} = -1 \][/tex]
Now, we'll find the corresponding [tex]\( y \)[/tex] values using the first equation [tex]\( y = x + 4 \)[/tex]:
For [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 2 + 4 = 6 \][/tex]
For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = -1 + 4 = 3 \][/tex]
Therefore, the points of intersection are:
[tex]\[ (-1, 3) \][/tex]
[tex]\[ (2, 6) \][/tex]
Looking at the given answer options:
A. [tex]\((-1, 3)\)[/tex] and [tex]\((2, 2)\)[/tex]
B. [tex]\((1, 3)\)[/tex] and [tex]\((-2, 2)\)[/tex]
C. [tex]\((-1, 3)\)[/tex] and [tex]\((2, 6)\)[/tex]
The correct answer that matches our solution is:
C. [tex]\((-1, 3)\)[/tex] and [tex]\((2, 6)\)[/tex]
1. [tex]\( y = x + 4 \)[/tex]
2. [tex]\( y = x^2 + 2 \)[/tex]
We need to find the points of intersection, which means we set the two equations equal to each other.
[tex]\[ x + 4 = x^2 + 2 \][/tex]
Re-arrange the equation to standard quadratic form:
[tex]\[ x^2 - x - 2 = 0 \][/tex]
We solve this quadratic equation using the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
where [tex]\( a = 1 \)[/tex], [tex]\( b = -1 \)[/tex], and [tex]\( c = -2 \)[/tex].
Calculate the discriminant ([tex]\( \Delta \)[/tex]):
[tex]\[ \Delta = b^2 - 4ac \][/tex]
[tex]\[ \Delta = (-1)^2 - 4(1)(-2) \][/tex]
[tex]\[ \Delta = 1 + 8 \][/tex]
[tex]\[ \Delta = 9 \][/tex]
Now, find the roots using the quadratic formula:
[tex]\[ x = \frac{-(-1) \pm \sqrt{9}}{2 \cdot 1} \][/tex]
[tex]\[ x = \frac{1 \pm 3}{2} \][/tex]
This gives us two solutions for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{1 + 3}{2} = 2 \][/tex]
[tex]\[ x = \frac{1 - 3}{2} = -1 \][/tex]
Now, we'll find the corresponding [tex]\( y \)[/tex] values using the first equation [tex]\( y = x + 4 \)[/tex]:
For [tex]\( x = 2 \)[/tex]:
[tex]\[ y = 2 + 4 = 6 \][/tex]
For [tex]\( x = -1 \)[/tex]:
[tex]\[ y = -1 + 4 = 3 \][/tex]
Therefore, the points of intersection are:
[tex]\[ (-1, 3) \][/tex]
[tex]\[ (2, 6) \][/tex]
Looking at the given answer options:
A. [tex]\((-1, 3)\)[/tex] and [tex]\((2, 2)\)[/tex]
B. [tex]\((1, 3)\)[/tex] and [tex]\((-2, 2)\)[/tex]
C. [tex]\((-1, 3)\)[/tex] and [tex]\((2, 6)\)[/tex]
The correct answer that matches our solution is:
C. [tex]\((-1, 3)\)[/tex] and [tex]\((2, 6)\)[/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.